122k views
3 votes
2(x + 5) + 2x - 7 simplify

User Tashanna
by
6.3k points

2 Answers

3 votes
Answer: 4xt3

Step-by-Step Explanation:
Simplify step by step
2(x+5)+2x-7
First you Distribute:
=
(
2
)
(
x
)
+
(
2
)
(
5
)
+
2
x
+

7
=
2
x
+
10
+
2
x
+

7
Then you have to Combine Like Terms
=
2
x
+
10
+
2
x
+

7
=
(
2
x
+
2
x
)
+
(
10
+

7
)
The answer would be =
4
x
+
3
User Andrey Dolgikh
by
6.3k points
1 vote

Answer:

I got 4x + 3 for my answer.

Explanation:

I distributed the 2 into the parenthasis. Then, combined like terms.

User Emachine
by
5.8k points